Current endoscopic surgical approaches for mediastinal resection - Suda, Takashi (Video-Assisted Thoracic Surgery; Vol 1 (October 2016): Video-Assisted Thoracic Surgery, 2016)
This paper reports on surgical mediastinal tumor resection at a single facility by means of single-port, video-assisted, thoracoscopic surgery (VATS) using a lateral intercostal approach together with initial outcomes (1). The approach reported by the authors resulted in commendable initial outcomes including mortality and morbidity.